Dirhodium Carboxylate Catalysts from 2‐Fenchyloxy or 2‐Menthyloxy Arylacetic Acids: Enantioselective C−H Insertion, Aromatic Addition and Oxonium Ylide Formation/Rearrangement. Issue 20 (23rd August 2021) - Buckley, Aoife M.; Crowley, Daniel C.; Brouder, Thomas A.; Ford, Alan; Rao Khandavilli, U. B.; Lawrence, Simon E.; Maguire, Anita R.
Abstract: A new class of dirhodium carboxylate catalysts have been designed and synthesized from 2‐fenchyloxy or 2‐menthyloxy arylacetic acids which display excellent enantioselectivity across a range of transformations of α‐diazocarbonyl compounds. The catalysts were successfully applied to enantioselective C−H insertion reactions of aryldiazoacetates and α‐diazo‐β‐oxosulfones affording the respective products in up to 93 % ee with excellent trans diastereoselectivity in most cases. Furthermore, efficient desymmetrization in an intramolecular C−H insertion was achieved. In addition, these catalysts prove highly enantioselective for intramolecular aromatic addition with up to 88 % ee, and oxonium ylide formation and rearrangement with up to 74 % ee. Abstract : A new class of rhodium carboxylate complexes, which contain phenylacetate ligands substituted with bulky chiral alkoxy substituents, has been prepared, and the application of these complexes in some representative carbene transfer processes of α‐diazocarbonyl compounds is described. Good enantioselectivity is obtained across a range of transformations.